Protein signaling and regulation of gene transcription in leukemia: role of the Casein Kinase II-Ikaros axis. Issue 3 (9th February 2016) - Gowda, Chandrika S; Song, Chunhua; Ding, Yali; Kapadia, Malika; Dovat, Sinisa
Abstract : Protein signaling and regulation of gene expression are the two major mechanisms that regulate cellular proliferation in leukemia. Discerning the function of these processes is essential for understanding the pathogenesis of leukemia and for developing the targeted therapies. Here, we provide an overview of one of the mechanisms that regulates gene transcription in leukemia. This mechanism involves the direct interaction between Casein Kinase II (CK2) and the Ikaros transcription factor. Ikaros ( IKZF1 ) functions as a master regulator of hematopoiesis and a tumor suppressor in acute lymphoblastic leukemia (ALL). Impaired Ikaros function results in the development of high-risk leukemia. Ikaros binds to the upstream regulatory elements of its target genes and regulates their transcription via chromatin remodeling. In vivo, Ikaros is a target for CK2, a pro-oncogenic kinase. CK2 directly phosphorylates Ikaros at multiple amino acids. Functional experiments showed that CK2-mediated phosphorylation of Ikaros, regulates Ikaros' DNA binding affinity, subcellular localization and protein stability. Recent studies revealed that phosphorylation of Ikaros by CK2 regulates Ikaros binding and repression of the terminal deoxytransferase (TdT) gene in normal thymocytes and in T-cell ALL. Available data suggest that the oncogenic activity of CK2 in leukemia involves functional inactivation of Ikaros and provide a rationale for CK2 inhibitors as a potential treatment for ALL.